PENERAPAN SISTEM PADI ORGANIK DENGAN APLIKASI AGENS HAYATI P60 DAN URINE KELINCI DI DESA PIASA KULON KABUPATEN BANYUMAS - Ahadiyat Yugi Rahayu; Sapto Nugroho Hadi; Ida Widiyawati (Panrita Abdi - Jurnal Pengabdian pada Masyarakat, 2019)
Abstract. Organic farming systems are environmentally friendly cultivation systems because without application of external inputs of synthetic fertilizers and pesticides. In order to increase the knowledge of understanding of farmers, demonstration plots of organic farming systems were carried out, especially on rice plants. The objective of this service activity is to increase knowledge and understanding and its application to the Ngudi Mratani farmer group regarding the organic method of rice systems through the application of microbial agent and rabbit urine based on results of research conducted at higher education institutions (Unsoed) that have the potential to be applied on land farmers and have high yield potency. The application of rabbit urine-based POC, coconut shell liquid smoke and Bio P 60 is applied to paddy planting demonstration plots and compared to other farmers who apply organic methods in different areas. The results of the activity showed that there was an increase in the absorption of knowledge, an increase in knowledge and understanding and the potential for success of 78.5%, 79.5% and 60%, respectively, which indicated good and potentially successful criteria. The yield of rice obtained in general by application organic rice system ranges from 4.6 to 6.0 t/ha. The application of rabbit urine POC showed the best results with a production of 6.02 t/ha.Keywords: Organic rice, rabbit liquid fertilizer (POC), coconut shell liquid smoke, Bio P 60.Abstrak. Sistem pertanian organik merupakan sistem budidaya yang ramah lingkungan karena tidak menggunakan input eksternal pupuk dan pestisida hayati. Untuk bisa meningkatkan pengetahuan pemahaman petani maka dilakukan demplot sistem pertanian organik khususnya pada tanaman padi. Tujuan dari kegiatan pengabdian ini adalah untuk meningkatkan pengetahuan dan pemahaman serta penerapannya pada kelompok tani Ngudi Mratani mengenai metode padi sistem organik dilakukan melalui aplikasi mikroba dan urine kelinci dari hasil penelitian yang telah dilakukan di lembaga pendidikan tinggi (Unsoed) yang memiliki potensi untuk diterapkan di lahan petani dan memiliki daya hasil yang cukup tinggi. Aplikasi POC berbasis urine kelinci, asap cair tempurung kelapa dan Bio P 60 diterapkan pada demplot pertanaman padi dan dibandingkan dengan petani lain yang menerapkan metode organik di area yang berbeda. Hasil kegiatan menunjukan bahwa terjadi peningkatak penyerapan pengetahuan, peningkatan pengetahuan dan pemahaman dan potensi keberhasilan masing-masing 78,5%, 79,5% dan 60% yang mengindikasikan kriteria baik dan berpotensi berhasil. Hasil padi yang diperoleh secara umum dari penerapan sistem padi organik ini berkisar antara 4,6 – 6,0 t/ha. Aplikasi POC urine kelinci menunjukan hasil terbaik dengan produksi 6,02 t/ha.Kata Kunci: Padi organik, POC urin kelinci, asap cair tempurung kelapa, Bio P 60